Hyperglycemia newly detected by glycated hemoglobin affects all-cause mortality in coronary artery disease patients: a retrospective cohort study. (September 2022) - Wei, Wen; Liang, Yan; Guo, Dachuan; Xu, Xinghao; Xu, Qingbo; Li, Shanggang; Li, Yuqi; Liu, Jin; Liu, Yong; Tu, Mei; Chen, Kaihong; Chen, Hong; et al.
Highlights: Hyperglycemia detected by HbA1c alone was common in coronary artery disease patients without known diabetes. Newly detected hyperglycemia was associated with increased long-term mortality in patients with coronary artery disease. HbA1c should be routinely detected in coronary artery disease patients to evaluate the glucose metabolic status. Abstract: Aims: We aim to assess the relationship between hyperglycemia and long-term prognosis in CAD patients without known diabetes. Methods: In this retrospective observational study, we enrolled 11, 384 CAD patients without known diabetes. Newly detected diabetes was defined as HbA1c ≥ 6.5 %, and prediabetes was defined as HbA1c ranging from 5.7 to 6.4 %.The association between hyperglycemia and long-term all-cause mortality was examined using Cox proportional hazards regression analysis. Results: According to HbA1c level, 8207 (72.1 %) patients had hyperglycemia, including 13.0 % with diabetes and 59.1 % with prediabetes. During a median follow-up of 4.9 years, 1157(10.2 %) patients died. Compared with normoglycemia, hyperglycemia was associated with increased risk for long-term mortality (adjusted hazard ratio for diabetes and prediabetes: 1.23 [95 % confidence interval (CI): 1.00 to 1.51] and 1.17 [95 % CI: 1.01 to 1.36], respectively). Conclusions: Hyperglycemia detected by HbA1c was common in CAD patients without known diabetes and was associated with increased long-term mortality. It is necessary to routinely use HbA1c to assess glucose metabolic status in CAD patients and treat hyperglycemia as early as possible to reduce the risk of adverse outcomes.